2005
DOI: 10.1002/masy.200551102
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Radical Polymerization of N‐Vinylpyrrolidone by Reversible Addition‐Fragmentation Chain Transfer Process

Abstract: Summary: Poly(N‐vinylpyrrolidone) (PNVP) was polymerized by RAFT process using diphenyldithiocarbamate of diethylmalonate (DPCM) as the reversible chain transfer agent in the presence of a small percentage of a conventional radical initiator (AIBN). The molar mass of the polymers synthesized by this method was found to increase with conversion and time. The presence of end group in the polymer chain could be confirmed by 1H NMR spectra. The molar masses calculated using 1H NMR spectroscopy and static light sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 18 publications
2
82
0
Order By: Relevance
“…[106] 71* [97] NVP [97] 72* [97] NVP [97] (S) [98] 70b* R = CH 3 AA/EAA [120] (EAA) [120] BA/EAA [120] DMA/EAA [120] DMAEA/EAA [120] VAc [121] 73 [56] NVP [56] VAc [56] 74* [106] VAc [106] 75a* S [122] A See footnotes A,B of Table 1. [123] 77* NVP [124] 78 [54] S [54] 78a R = CH 3 78b R = Ph [55] S [55] 80 [55] S [55] 81 [55] S [55] [55] S [55] 83 [55] S [55] 84 [55] (S) [55] [55] (S) [55] 86 [125] BA MA/MAA [126] A See footnotes A,B of Table 1. [47] S [40,47] 88* (MA [96] S [96] ) 89* MMA [127] A See footnotes A,B of Table 1.…”
Section: Side Reactions In Raft Polymerizationmentioning
confidence: 99%
“…[106] 71* [97] NVP [97] 72* [97] NVP [97] (S) [98] 70b* R = CH 3 AA/EAA [120] (EAA) [120] BA/EAA [120] DMA/EAA [120] DMAEA/EAA [120] VAc [121] 73 [56] NVP [56] VAc [56] 74* [106] VAc [106] 75a* S [122] A See footnotes A,B of Table 1. [123] 77* NVP [124] 78 [54] S [54] 78a R = CH 3 78b R = Ph [55] S [55] 80 [55] S [55] 81 [55] S [55] [55] S [55] 83 [55] S [55] 84 [55] (S) [55] [55] (S) [55] 86 [125] BA MA/MAA [126] A See footnotes A,B of Table 1. [47] S [40,47] 88* (MA [96] S [96] ) 89* MMA [127] A See footnotes A,B of Table 1.…”
Section: Side Reactions In Raft Polymerizationmentioning
confidence: 99%
“…The CTA 5 was then used to polymerise N-vinylpyrrolidone (NVP) in a controlled manner to give PVP chains with alkyne end groups (Supplementary Information, Scheme S3). In the literature [38][39][40][41][42] , both xanthate and dithiocarbamate chain transfer agents were shown to be good candidates for polymerising NVP, a monomer that is a member of the "less activated monomers" (LAM) class described by Keddie et al 43 Furthermore, Patel et al 44 and Akeroyd et al 31 reported the preparation of alkyne-terminated RAFT agents which were used for preparing "macro-RAFT agents" or clickable polymers respectively. The ratio RAFT agent : initiator (AIBN) was optimised to obtain relatively high conversion and good control of the polymerisation, and we found that 1:0.7 was a good compromise, giving a monomer conversion and a Ɖ M of 80% and 1.4 respectively.…”
mentioning
confidence: 99%
“…Additionally this monomer is incompatible with ATRP due to its tendency to form complexes with transition metal catalysts. Thus it was not until relatively recently that PVP has been made in a controlled fashion using controlled radical polymerisation techniques such as RAFT [48][49][50][51][52][53][54] and NMP, 49 mechanisms with a high tolerance towards impurities and functional groups, in addition to a wide range of temperatures and solvents. RAFT was therefore chosen as an efficient methodology for the synthesis of the end functionalised polymers described herein, exploiting the use of functionalised CTAs to impart end functionality to the nascent polymer.…”
Section: Synthesis Of End Functionalised Polymer Additivesmentioning
confidence: 99%
“…34 Poly(N-vinyl pyrrolidone) (PVP) is a widely exploited, water soluble, biocompatible polymer with a wide range of commercial applications including as an adhesive, a binder in the pharmaceutical industry, in coatings and even as a food additive. PVP can be readily polymerized with a high degree of control by RAFT polymerization [45][46][47][48][49][50][51][52][53][54] , less efficiently by nitroxide mediated radical polymerization 49,55,56 and not at all by other controlled/living polymerization mechanisms due to the presence of the amide functionality. Thus PVP is an interesting (and useful) polymer to demonstrate the concept of using a functionalized RAFT agent with CF groups as part of the R group for the synthesis of end functionalized polymers.…”
Section: Introductionmentioning
confidence: 99%